Generative computer-aided design: multi-modality large-scale direct physical production. Issue 1 (2nd January 2017) - Chen, Lujie; Sass, Lawrence
ABSTRACT: A rapid prototyping system for creating large-scale physical objects directly from computer models is introduced. Several production modalities incorporated in the system can be used to produce objects in different scales and types. Parts of the objects are generated by computational algorithms with appealing features that enable CNC manufacturing and facilitate manual assembly. Experiments have shown that man is an important factor of the production process even though the system has automated majority of part generation and fabrication. We show several large models created from the system, discuss problems associated with large-scale prototyping, and present potential applications of the proposed methods. GRAPHICAL ABSTRACT: